PENYUSUNAN RENCANA PELAKSANAAN PEKERJAAN BRANTAS RIVER CHECK DAM 10 (BRCD-10) KOTA BATU MALANG - Gunawan Wibisono (Prokons: Jurnal Teknik Sipil, 2013)
Uncertain seasonal changes lately, causing a lot of flooding, especially in the Brantas River Basin, causing several volcanoes in the upper reaches of the Brantas River are also often carries sediment in case of floods or heavy rain, one of these volcanoes are Arjuno Mount, many of carrying materials sedimentation. One way that can be used to reduce and control the sediment, along the Brantas River by building Sabo Dam. Sabo Dam construction plan targets not only in the upper Brantas River, but also in downstream areas of the Brantas River. Sabo Dam construction by the Contractor with Grade 7 is expected to be completed in accordance with the planning purpose, because the good planning and direction will be able to save time, costs and problems (risks) that will bring the work to the activities of its main objectives, namely the right time, right cost and right quality. Implementation work methods to used for complete the development work Sabo Dam is coffering which planned uses "Phase Half-Span", which spans half a dodger and the other half worked for the evader landscape flow. The cost of implementing the budget obtained after analysis is Rp. 5,212,063,817.11 to the difference obtained Rp. 342,856,956.89 or 6,172 % from the value of the contract, the implementation quality of existing jobs on Sabo Dam work has been largely in accordance with the technical specifications have been prepared. Deviations occur, the laying material (aggregates and sand) that is not clean, while the implementation of existing K3 is in conformity with the regulations to be referenced by the Contractor in the preparation of safety plan, only for the application to use the APD is not yet implemented. Keywords: project planning, sabo dams, check dams, waterworks